THE COMMUNICATION OF PERFECTIONISM AND OPTIMISM AT STUDENTS WITH THE DIFFERENT LEVEL OF THE ACADEMIC PROGRESS - Kuznetsova, Maria (PSYCHOLOGICAL JOURNAL, 2017)
In the article are analysed the results of an empirical research of interrelation of perfectionism and optimism at students with the different level of the academic progress. Two levels of manifestation of optimism – strategic (beliefs and semantic installations of the personality) and operational and tactical (style of processing of the current information by the subject, i.e. optimistic attributive style) are allocated. The assumptions that were checked: 1) indicators of three types of the perfectionism (focused on itself, focused on others and socially ordered) are connected with optimism of students, and the orientation of these communications for different types of perfectionism can be various; 2) these interrelations are traced as at the «strategic», «personal» level of the generalized beliefs, and at the «subject», «operational» level; 3) the structure of these interrelations at in time and the low academic progress students is various; in the time students will surpass the low academic progress students in ability to rely on optimistic installations and optimistic attributive style for overcoming shortcomings of perfectionism. In a research with participation of 290 students it has been shown that indicators only of two types of perfectionism – focused on itself and socially ordered are connected with indicators of optimism. At the same time, as optimism of strategic level (optimistic dispositions), and optimism operational and tactical (optimistic attributive style) were connected with perfectionism indicators in a similar way: with focused on itself – back, and with socially ordered – directly. Students with the developed system of optimistic dispositions, are much more rare than others show signs of the perfectionistic requirements imposed to on themselves. Pessimistic beliefs and considerable decrease in optimistic attributions are characteristic of students with the expressed self-focused perfectionism and, perhaps, is one of factors of their emotional disadaptation. The low academic progress students, unlike the high ones, aren’t able to use dispositional optimism as a resource for compensation of the shortcomings inherent in perfectionism focused on itself. At high academic progress students, unlike the low ones, actively use both world outlook, and operational and tactical optimism for strengthening of advantages of socially ordered perfectionism. Perceiving a social environment as «excessively exacting», «setting unreasonably difficult tasks», they support at themselves steady positive mood. At high academic progress students a peculiar affective and communicative complex thanks to which they can overcome without prejudice to themselves potentially stressful situations arising because of failure in the solution of any tasks (for example, educational).